A label- and enzyme-free fluorescence assay based on thioflavin T–induced G-quadruplexes for the detection of telomerase activity. Issue 1 (January 2023) - Chen, Zhe; Wang, Yunxia
A label- and enzyme-free fluorescence assay based on thioflavin T–induced G-quadruplexes is developed to sensitively and specifically detect telomerase activity. Thioflavin T has a dual role as an efficient inducer and fluorescent probe, and the incorporation of thioflavin T into the thioflavin T–induced G-quadruplexes results in an intense fluorescence enhancement. In the presence of thioflavin T and K +, G-quadruplexes are formed by elongation of the telomerase substrate primer that is catalyzed by telomerase extracted from cancer cells. Thus, the telomerase activity in cancer cell extracts can be evaluated by measuring the thioflavin T fluorescence. More importantly, thioflavin T can specifically recognize and bind to G-quadruplexes, whereas it cannot recognize single- and double-stranded DNAs, which leads to the thioflavin T–based fluorescence assay exhibiting a reduced background and improved signal-to-noise ratio. As a result, the proposed assay has the linear range from 5 to 200 HeLa cells and the detection limit is 34 HeLa cells, which holds great potential for use in the detection of telomerase activity and the diagnosis of cancer.